German economy defying a turbulent and uncertain environment - Claus Michelsen; Martin Bruns; Marius Clemens; Max Hanisch; Simon Junker; Konstantin A. Cholodilin; Thore Schlaak (DIW Weekly Report, 2019)
After a turbulent summer, marked by a weak second and a likely stronger third quarter, the German economy should return to an average pace of growth and end up with a growth rate of 0.9 percent in 2019. Despite the more subdued pace, capacity utilization remains high; employment growth is continuing, albeit more slowly; and the trend of foreign demand is weakening but remains buoyant overall. In this economic setting, companies are expanding their investments, yet are likely to act cautiously due to imminent upheavals in global trade.
Keywords: E32; E66; F01; 330; business cycle forecast; ecoomic outlook